Sorption of phenols and flavonoids on activated charcoal improves protein metabolism, antioxidant status, immunity, and intestinal morphology in broilers - Zhang, Ying; Fu, Xiaoqi; Wang, Lixue; Guo, Xiangyue; Dong, Bing (Frontiers in Veterinary Science, 2024)
Previous studies revealed that activated charcoal sorption of Chinese herb extracts were more effective than activated charcoal. This study was to investigate whether phenols and flavonoids had an effect on the nutrient metabolism, antioxidant activity, immunity, and intestinal morphology in broilers. Seven diets [basal diet (CON); CON supplemented with 450 mg/kg of activated charcoal (AC); CON supplemented with 250, 500, 750, 1000, or 7500 mg/kg of phenolic acids and flavonoids (PF) to AC (PFAC). PFAC was the complex of AC sorption of PF in the ratio of 9:1. The dietary treatments for broilers lasted for 42 days. Results showed that on d 21, all doses of PFAC altered serum levels of total protein, albumin, and creatinine (P < 0.05), compared to AC. Both PFAC and AC altered HDL-, LDL-, and VLDL-cholesterol levels compared to CON (P < 0.05). PFAC at 500 mg/kg (450 mg/kg AC+ 50 mg/kg phenolic acids and flavonoids) increased serum IgA and IgM (P < 0.05), but AC at 450 mg/kg did not, comparing to CON. On d 42, breast muscle and thigh muscle of PFAC treated broilers had higher scavenging activities of free radicals compared to CON (P < 0.05), but AC had no such effect. PFAC increased villus height in duodenum, jejunum, and in ileum at 500 mg/kg compared to CON (P < 0.05), but AC had no such response. PFAC at 500 mg/kg effectively improved protein and lipid metabolism, antioxidant, and intestinal morphology, but AC had no such effect at the similar dose. Excessive PFAC (7500 mg/kg) showed no significant side effect for broiler growth, liver damage or hematology. These results suggested that phenols and flavonoids, cooperated with activated charcoal, represented a majority of functions of the herb extract from multiple Chinese medicinal herbs.